An Alternative to the Traditional Radiocapitellar Line for Pediatric Forearm Radiograph Assessment in Monteggia Fracture. Issue 3 (March 2020) - Wang, Cui; Su, Yuxi
Abstract : Objective: To find a new reference for assessment of pediatric forearm radiographs besides the traditional RCL. Methods: RCLs were drawn on the anteroposterior (AP) and lateral radiographs of 170 normal pediatric forearms. Three lines were drawn on each radiograph: the first was drawn along the longitudinal center of the radial neck (N-line); the second, along the radial shaft (S-line); and the third, through the midpoints of the proximal and distal radial physes (P-line). Results: The P-line was least likely to miss the capitellum on both AP views and lateral views, and the P-line most frequently passed through the central third of the capitellum on both AP views and lateral views. Conclusions: Our proposed radiocapitellar P-line was found to be much more reliable in younger children than traditional RCLs.